UPAYA PENINGKATAN KOMPETENSI GURU DALAM MELAKSANAKAN PROSES BELAJAR MENGAJAR MELALUI SUPERVISI AKADEMIK DI SDN 011 BUKIT RAYA SINGINGI HILIR KECAMATAN SINGINGI HILIR - Wartini Wartini (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
The purpose of this study is to improve the ability of teachers to implement PBM through academic supervision. The designof this study is qualitative research with the School Action Research approach. The results showed that the level of ability toimplement PBM of subject teachers increased significantly, in Cycle I the score was 66.8 (good criteria), Cycle II scored71.4 (good criteria), and Cycle III had an average value of 80 , 2 (criteria are very good). Based on the results of the study itcan be concluded that the teacher's ability to implement PBM through academic supervision has increased. Based onconclusions, suggestions were made for teachers to continue to improve their abilities with guidance from schoolsupervisors/ principals and to learn independently with the use of technology